Effectiveness using recycled polyethylene terephthalate (pet) and mineral fillers as additive in asphalt mixture for binder course - Norhaizan, Ismail (2014)
Polyethylene Terephthalate (PET) is the most popular recycle plastic in the world because it is highest polymer in numbering system for plastic recycling. In this research, recycle PET used as a material in the mix asphalt modification. The objectives of this research were to determine the aggregate in asphalt mixture for binder course and to evaluate the effect usage recycle PET as additive in modified asphalt mixture by determining the stiffness properties at temperature 20° Celsius. In experiment conducted, there are two type of mineral fillers used which are Portland cement and lime for control and modified samples with 5.5% was added in asphalt mixture. The modified asphalt mixture consists of recycle PET in pallet form. The recycled PET was used from 2% to 10% of weight asphalt mixture with sieve size from 2.36mm to 1.18mm. The 80/100 penetration grade of bitumen was used in this experiment and this grade is usually used in Malaysia. The 5% weight of bitumen content was used in this experiment as followed the standard specification from Public Work Department for binder course (ACB 28). The sample testing performed using Indirect Tensile Stiffness Modulus Test (ITSM) to evaluate the stiffness properties of modified asphalt mixture. The result shows that the percentage of PET content in modified asphalt is higher stiffness compared to unmodified asphalt. All PET modified asphalt are more stiff rather than unmodified. The maximum modulus stiffness occurs at 4% PET content using filler Portland cement and 2% PET content using filler lime in asphalt mixture. In binder course layer of pavement structure, the 4% PET is high modulus stiffness compare with modified asphalt. In conclusion the value of modified asphalt using fillers such as lime can increase the stiffness properties compared to using Portland cement. In term of economic value, the recycle PET is a good material to use in construction because it could be improve the life service and also reducing the cost of road construction. Furthermore the material which is bitumen is cheaper and easy to obtain. The finding indicates that, the recycled PET has ability to improve the stiffness properties in modified asphalt mixture.